The influence of the hydrothermal regime on the migration of calcium carbonates in dark gray podzolized soils on slopes with different exposures in Kharkiv region - Solovei, V. B.; Trotsenko, О. О. (AgroChemistry and Soil Science, 2025)
The paper presents the results of a study on the hydrothermal regime of dark gray podzolized soils (Luvic Greyzemic Phaeozem (Loamic)) on slopes with different exposures and the seasonal dynamics of calcium carbonate migration within their profiles. The research was conducted in the Kharkiv region of Ukraine at four closely located sites: on slopes with northwestern and southeastern exposures, as well as on a flat area and at the bottom of a gully. It was established that the seasonal depth of carbonate occurrence, as an important morphological characteristic of the soil, largely depends on the dynamics of temperature and moisture content in the soil profile, which are determined by slope exposure. Soil moisture content was measured using the thermostat-weight method, with samples taken from the 0–120 cm layer at 10 cm intervals. Soil temperature was recorded continuously at 30-minute intervals throughout the study period using thermosensors equipped with DS18B20 digital sensors, installed at 10 cm intervals (down to 120 cm); one sensor placed on the soil surface (0 cm). Precipitation amounts were recorded using a rain gauge. Snow cover depth and coverage extent were documented daily when snow was present. Special attention was paid to the role of seasonal changes in soil moisture in the processes of carbonate migration and sedimentation. The mechanisms of vertical differentiation of inorganic carbon in the soil profile in the form of carbonates are described. The study analyzes migration models and their dependence on climatic, hydrological, and biological factors. It was found that on the northwestern slope, where the soil remains in a state of elevated moisture for a prolonged period, downward vertical migration of dissolved carbonates predominates. On the southeastern slope, under conditions of high insolation and intense evaporation, carbonates accumulate in the upper horizons. On the flat area, intermediate hydrothermal soil characteristics (relative to the slopes) were observed — seasonal fluctuations in temperature and moisture result in bidirectional carbonate migration: leaching into lower horizons in autumn and winter, and upward movement in spring. The study also considers the potential indicative role of carbonate concretions in the soil profile — as evidence of migration–accumulation processes, the direction and intensity of carbonate migration, and changes in hydrothermal conditions during soil formation. It is noted that concretions may be of relict origin from the parent material or the result of pedogenic processes. The observations demonstrate that topography, hydrothermal conditions, and biological activity are key factors determining the distribution and dynamics of carbonates in the profiles of the studied dark gray podzolized soils.